Impact of auxeticity on mechanical properties of 3D woven auxetic reinforced thermoplastic composites. Issue 2 (3rd November 2022) - Ullah, Tehseen; Hussain, Muzzamal; Ali, Mumtaz; Umair, Muhammad
Abstract: 3D woven composites are currently used in high‐tech applications due to their better mechanical properties than 2D laminated composites. To further enhance the mechanical performance of 3D woven composites, auxetic structures can be used as reinforcement. The auxetic structures showed better mechanical properties due to bidimensional energy dissipation capability. Orthogonal 3D woven structures showed inherent auxetic nature, however, the use of brittle thermoset resins in composites fully limits their auxeticity. To overcome this issue, three types of 3D woven auxetic structures (warp, weft, and bidirectional interlocks) were developed and used as reinforcement with thermoplastic resins (PC and PVB). Auxeticity of woven reinforcement, and tensile, flexural (3‐point), and short beam shear (SBS) tests of composites were conducted. Auxeticity results revealed that the warp interlock structure showed the highest auxeticity, while the bidirectional interlock structure exhibited the least auxeticity due to the high number of intersections and crimp %. Furthermore, warp interlock composite structure showed 47%, 49.5%, and 37% higher tensile, flexural, and shear strength values, respectively than bidirectional interlock structure in warp direction with PC resin. The overall results showed that auxetic reinforcement improved the mechanical performance of 3D woven composites. Abstract : Improve the mechanical performance of thermoplastic composites by incorporating the 3D woven auxetic reinforcement.